1993
DOI: 10.1007/bf00196440
|View full text |Cite
|
Sign up to set email alerts
|

Axillary hidradenitis suppurativa: wide excision and flap coverage is best

Abstract: Eur J Plast Surg (1993) Summary. The extent of axillary excision and method of closure in 17 patients (29 axillae) with symptomatic chronic axillary hidradenitis suppurativa was analyzed. Limited excision of only the diseased skin led to recurrence in 2 of 3 patients, and excision of the hair-bearing skin alone, in 2 of 5 patients. There was no recurrence in 11 patients after wide excision. Some patients had more than one procedure. Three of four patients who had skin grafts used for closure, developed axill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…15 In an attempt to reduce the incidence of recurrent disease further, wide local excision (2 cm beyond the hair bearing skin) was performed. This was suggested to be the best form of treatment in an initial study of nine patients 11 and in this series where this was effected, there was no disease recurrence. However, this method of treatment did not reach statistical significance when compared to excision of all the hair bearing skin (P = 0.18, Fischer's exact test).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…15 In an attempt to reduce the incidence of recurrent disease further, wide local excision (2 cm beyond the hair bearing skin) was performed. This was suggested to be the best form of treatment in an initial study of nine patients 11 and in this series where this was effected, there was no disease recurrence. However, this method of treatment did not reach statistical significance when compared to excision of all the hair bearing skin (P = 0.18, Fischer's exact test).…”
Section: Discussionmentioning
confidence: 84%
“…A number of studies have shown that inadequate excision is the major cause of recurrence. 4,11,14 Excision of all the hair bearing skin is a more extensive resection. Most of the apocrine glands are excised with this type of procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation